Artificial feeding in Surgery. - Mate, Miguel; Llano, Ramiro; León, Isidro; Parodi, José; Pradines, Jorge (Cirugía del Uruguay, 1983)
The authors ex pose their experience in 100 patients treated in almost 5 years of activity, analizing: age, malnutrition degree and diagnosis of the assisted population. The value the answer to terapeutic measures, specially in albumin blood level and weight. The discuss the malnutrition degreee importance in order to get a RNM satisfactory answer, con.cluding that in severe malnutrition, the answer is statistically insign ificant. They conclude that their patients are of h igh surgical riske, although increasing of severity with increasing of surgical risk was seen in a few number of cases.